Intravascular Lithotripsy for Underexpanded Stent in Heavily Calcified Coronary Artery Disease. (15th July 2022) - Raxwal, Tejas; Balhara, Cauvery; Parekh, Dipak
Abstract : Objective . Can intravascular lithotripsy safely modify calcium in an underexpanded stent and result in optimal expansion and improved outcome? Coronary artery calcification results in difficulty with stent delivery and expansion and is associated with adverse outcomes. Intravascular lithotripsy (IVL) by delivering acoustic pressure waves modifies calcium plaque that improve vessel compliance resulting in optimizing stent deployment. Results . A 63-year-old patient presented with acute coronary syndrome with symptoms of unstable angina who underwent angiography that showed calcified right coronary artery which was treated with balloon angioplasty and stenting with drug eluting stent. However, after multiple inflations with noncompliant balloon, the patient was noted to have persistent residual in stent stenosis of 70%. Stenotic lesion in poorly expanded stent was treated with Shockwave C2 Coronary Intravascular Lithotripsy catheter resulting in 0% residual stenosis. The patient was followed for major adverse cardiovascular events at 30 days and 12 months. The patient remained MACE free at 30 days and 12 months. Conclusions . Coronary IVL safely and effectively facilitated stent expansion in severely calcified lesion in a poorly expanded stent with MACE free at 12-month follow-up.